Learning Innovation: Creating an Effective and Enjoyable Learning Model in Elementary Madrasahs - Subairi, Agus (MSJ : Majority Science Journal, 2025)
This study aims to identify and analyze various innovations in effective and enjoyable learning models that have been implemented in Madrasah Ibtidaiyah (MI), in order to improve the quality of basic education in accordance with the characteristics of early age learners. The method used in this study is the Systematic Literature Review (SLR), which allows researchers to filter, evaluate, and synthesize previous research results systematically and in a structured manner from various credible academic sources. This approach involves the stages of literature search, selection based on strict criteria, and thematic analysis of innovative learning models. The results of the study indicate that learning in MI requires an approach that is able to combine Islamic values ​​with active and contextual learning methods. One model that has proven effective is Project-Based Learning (PjBL), which can increase student engagement, conceptual understanding, and the development of 21st century skills. In addition, the integration of technology in learning also provides positive potential in creating interactive learning experiences, although it still faces technical and resource constraints. The principles of enjoyable learning such as differentiation, active learning, and emotional involvement are the keys to the successful implementation of this innovation. These findings are expected to be the basis for developing learning practices that are more relevant, effective, and appropriate to the socio-cultural context of MI.